The Effect Of Using Augmented Reality Media One The Learning Results of The ‘Caping Ngancak’ Dance for Grade V Students At Sdn 2 - Cut Rifhka; Aida Fitri; Intan Safiah (Catharsis, 2023)
In learning arts and culture, there are still many students who do not understand traditional dance material, especially the ‘caping ngancak’ dance. The implementation of learning implemented by teachers is still teacher-centered, teachers do not involve students enough so that there are still many students who are less active. For this reason, it is necessary to implement learning that can make students active in learning arts and culture. So a medium was used in this research, namely Augmented Reality media. The formulation of the problem in this research is "is there an influence of the use of Augmented Reality on student learning outcomes in the Caping Ngancak dance material in class V SDN 2 Kota Bakti Kab. Pidie?” This research aims to determine the effect of using Augmented Reality on student learning outcomes in the Caping Ngancak dance material. The approach in this research is a quantitative approach, the type of research is True Experimental with a Pretest Posttest Control Group Design. The research population was all class V students of SDN 2 Kota Bakti Kab. Pidie, by taking samples of students from classes VA and VB. The data collection technique uses tests in the form of pretest and posttest, while the data analysis technique uses SPSS Statistics 24 and hypothesis testing uses the independent t-test. The results of hypothesis testing with independent t-test statistics obtained a significance value (2-tailed) of 0.000 < 0.05. So the decision making criteria are H_a accepted and H_0 rejected. Thus, it can be concluded that there is an influence of the use of Augmented Reality media on student learning outcomes in the Caping Ngancak dance material in class V at SDN 2 Kota Bakti Kab. Pidie.